PWE-160 Interferon Alpha Therapy for Metastatic Neuroendocrine Tumours: A Retrospective Study. (4th June 2013) - Mirvis, E; Mandair, D; Garcia-Hernandez, J; Toumpanakis, C; Mullan, M; Caplin, M
Abstract : Introduction: Interferon alpha has been used in the management of NETs for over 20 years. It has generally not been popular due to perceived lack of efficacy and due to toxicity profile. Currently molecular targeted medical therapies such as mTOR inhibitors and tyrosine kinase inhibitors are promoted but studies demonstrate only modest anti-tumour effect and time to progression (TTP) with not insignificant toxicity. Aim: To perform a retrospective analysis of Interferon alpha (IFNα) in patients with metastatic NET and assess efficacy and toxicity. Methods: We identified 37 patients treated with IFNα 3 – 5 million units x 3 per week between 2000–2012. Mean age 58.6 (24–88) years; 26:11 male:female; 21 midgut primary, 7 pancreatic, 1 hindgut, 1 bronchial, 1 thymic and 6 unknown. Histology: G1 49%; G2 41%; G3 5%: unknown 5%. 76% were also on somatostatin analogue. 65% had recorded progressive disease at disease onset. CT/MRI imaging; urine 5HIAA and plasma chromagranin A (CgA) and toxicities were recorded. Results: 9 (24%) withdrew before 3 months because of toxicity, progressive disease or death. On intention to treat analysis: 1 (3%) had complete response; 1 (3%) partial response; 26 (70%) had at least 3 months of stable disease. The median TTP was 14 months. Median 5HIAA fell from 54 to 29 umol/24h at 6 months (NS) and CgA from 138 to 121pmol/l at 6 months (NS). 38% had WHO grade 1–2 haematological toxicity and 19% grade 3–4. The only other grade 3–4 toxicity was depression in 1 patient and 22% had grade 1–2 depression. Other grade 1–2 toxicities > 10% included flu-like symptoms 24%, fatigue 16%, hypothyroidism 11%, dry skin 14%. Conclusion: Although there is toxicity which affects management in up to 1/3rd of patients the remaining patients tolerated therapy well. IFNα demonstrated efficacy in at least inducing or maintaining stable disease in most patients (76%). The median TTP is at least similar to other molecular targeted therapies. Those patients who were going to be intolerant or progress usually did so within the first 3 months of treatment. It would be appropriate to perform prospective randomised studies utilising IFNα and also better assess quality of life. Disclosure of Interest: None Declared.